Coupled inductor‐based single‐stage high gain DC–AC buck–boost inverter. Issue 8 (1st June 2016) - Sreekanth, T.; Lakshminarasamma, N.; Mishra, Mahesh Kumar
Abstract : Two stage conversion systems (TSCSs) normally use either boost converter or high gain dc–dc converter along with dc–ac inverter in order to transfer power from low input voltage dc source to high voltage ac load. When these TSCSs operate at extremely low input voltages, the boost converter has to operate at extremely high duty ratios. This in turn results in more losses and reverse recovery problems. Usage of high gain dc–dc converter results in more number of components, increase in control complexity and decrease in reliability. Single‐stage conversion systems (SSCSs) are formed by merging both dc–dc and dc–ac conversion processes. These SSCSs have advantages like low loss, more compactness and less reverse recovery problems. In this study, a high gain coupled inductor‐based single‐phase SSCS is presented. This SSCS topology has many desirable features such as high gain, less switching losses, free from leakage inductance adverse effects and compact. Principle of operation, steady‐state analysis and design of the proposed topology are described in detail. MATLAB simulation results of the proposed topology and experimental results using DSP28335‐based experimental setup are presented to validate the proposed scheme.